Investigação de componentes químicos da casca do caule de Luehea divaricata martius (malvaceae) e suas potenciais atividades biológicas - Cunha, Sabrina Bassaldua da (2016)
Luehea divaricata, known as açoita-cavalo , is a Brazilian native species and has few reported in the literature. Phytochemical investigation of the methanolic crude extract and its fractions (acid ethereal, basic ethereal, basic ethyl acetate, neutral dichloromethane, neutral ethyl acetate and neutral hexane) from stem bark of L. divaricata (Malvaceae) resulted in the isolation of seven compounds: bis (2-ethyl-heptyl) ftalate (26), one triterpene friedelin (28), mixture of the terpenes α- (27) and β-amyrin (1), two steroids β-sitosterol (29) and glycosyl β-sisotsterol (14), and two flavonoids known as catechin (22) and epicatechin (8), which are diasteroisomers, respectively. The compound friedelin (28), isolated from ethereal acid fraction, was identified for first time in genus Luehea. The structures of the isolated metabolites were elucidated by 1H and 13C NMR in one- and two-dimensional analysis, by X-ray diffraction, melting point, beyond comparison with standard samples where possible and data available from literature. The extract, fractions and isolated compounds were tested for their antimicrobial activity and antioxidant capacity. Crude methanolic extract, fractions and isolated compounds from acid-base fractionation showed effective antibacterial (Gram-positive and Gram-negative) and antifungal activities for the strains tested. Basic and neutral ethyl acetate fractions showed good antioxidant potential when tested against their capacity. Thus, the study of phytochemical and pharmacological activities of the identified compounds from stem bark of L. divaricata expands knowledge alluding to chemotaxonomy and justifies its use in ethnopharmacology because, to date, only studies with other aerial parts were performed.